EDITORIAL - Yenque Dedios, Julio (2006)
We are before a change of government and the question we ask ourselves each time there is a change of government is: Will the next government give the necessary importance to education?. Every intellectual knows that to reach the development of a country it is a must to invest in education, science and technology and that scientific research is a necessary basic component. In the research field, Peru is the country which invest less compared to other South American countries.